Meagher, Gummow and Lehane's equity doctrines and remedies - Heydon, John D.; Leeming, Mark 1969-; Turner, P. G. ca. 20./21. Jh (LexisNexis Butterworths Australia, 2015)
"This new edition includes analysis of developments in Australia and the common law world over the past 12 years. It deals with all fundamental equitable doctrines and remedies, save for trusts, and covers the development of equity and its history in the United Kingdom and Australia, including the effects of the Judicature system."
Keywords: Equity / Australia; Equitable remedies / Australia; Equitable remedies; Equity; Australia; Australien